Skip to content

Commit

Permalink
Updated tests and examples
Browse files Browse the repository at this point in the history
  • Loading branch information
RJDennis committed Apr 6, 2022
1 parent 83dcc13 commit 5473233
Show file tree
Hide file tree
Showing 8 changed files with 16 additions and 0 deletions.
2 changes: 2 additions & 0 deletions examples/example_four/model1a.txt
Original file line number Diff line number Diff line change
Expand Up @@ -21,6 +21,8 @@ parameters:
sd = 0.01
end

solvers: Any

equations:
k(+1) = (1.0 - δ)*k + exp(z)*k^α - c
c^(-σ) = β*muc(+1)*(1.0 - δ + α*exp(z(+1))*k(+1)^(α - 1.0))
Expand Down
2 changes: 2 additions & 0 deletions examples/example_one/model1a.txt
Original file line number Diff line number Diff line change
Expand Up @@ -21,6 +21,8 @@ parameters:
sd = 0.01
end

solvers: Any

equations:
k(+1) = (1.0 - δ)*k + exp(z)*k^α - c
c^(-σ) = β*muc(+1)*(1.0 - δ + α*exp(z(+1))*k(+1)^(α - 1.0))
Expand Down
2 changes: 2 additions & 0 deletions examples/example_three/model5a.txt
Original file line number Diff line number Diff line change
Expand Up @@ -28,6 +28,8 @@ sd_2 = 0.025
sd_3 = 0.003
end

solvers: Any

equations:
z(+1) = ρ1*z + sd_1*η1
ϵ(+1) = ρ2*ϵ + sd_2*η2
Expand Down
2 changes: 2 additions & 0 deletions examples/example_two/model3b.txt
Original file line number Diff line number Diff line change
Expand Up @@ -20,6 +20,8 @@ parameters:
ρ = 0.8
end

solvers: Any

equations:
exp(k(+1)) = (1.0 - δ)*exp(k) + exp(z)*exp(k)^α - exp(c)
(exp(c) - γ*exp(c(-1)))^(-σ) = β*muc(+1)*(1.0 - δ + α*exp(z(+1))*exp(k(+1))^(α - 1.0))
Expand Down
2 changes: 2 additions & 0 deletions test/model1a.txt
Original file line number Diff line number Diff line change
Expand Up @@ -21,6 +21,8 @@ parameters:
sd = 0.01
end

solvers: Any

equations:
k(+1) = (1.0 - δ)*k + exp(z)*k^α - c
c^(-σ) = β*muc(+1)*(1.0 - δ + α*exp(z(+1))*k(+1)^(α - 1.0))
Expand Down
2 changes: 2 additions & 0 deletions test/model1b.txt
Original file line number Diff line number Diff line change
Expand Up @@ -19,6 +19,8 @@ parameters:
ρ = 0.8
end

solvers: Any

equations:
k(+1) = (1.0 - δ)*k + exp(z)*k^α - c
c^(-σ) = β*muc(+1)*(1.0 - δ + α*exp(z(+1))*k(+1)^(α - 1.0))
Expand Down
2 changes: 2 additions & 0 deletions test/model2a.txt
Original file line number Diff line number Diff line change
Expand Up @@ -21,6 +21,8 @@ parameters:
sd = 0.01
end

solvers: Any

equations:
k(+1) = (1.0 - δ)*k + exp(z)*k^α - c
c^(-σ) = β*muc(+1)*(1.0 - δ + α*exp(z(+1))*k(+1)^(α - 1.0))
Expand Down
2 changes: 2 additions & 0 deletions test/model2b.txt
Original file line number Diff line number Diff line change
Expand Up @@ -19,6 +19,8 @@ parameters:
ρ = 0.8
end

solvers: Any

equations:
k(+1) = (1.0 - δ)*k + exp(z)*k^α - c
c^(-σ) = β*muc(+1)*(1.0 - δ + α*exp(z(+1))*k(+1)^(α - 1.0))
Expand Down

0 comments on commit 5473233

Please sign in to comment.